The Insights of Academician Evgeni Mateev about the Transition towards a New Type of Civilization (UNWE Yearbook, 2011)
In this publication I reveal the unique insights of acad. E. Mateev about the inevitability and the irreversibility of the society’s movement towards a new type of a civilization. The insights of acad. E Mateev about the moving forces of the motion and the development towards a new type of a civilization are presented, insights about the planning as an adequate tool for the transition towards the creation of a new type of civilization. The insights of acad. E. Mateev about the necessity and the possibility of permanent and systematic development and elaboration of the planning are revealed. The insights of acad. E. Mateev about the sings and the criteria about the evaluation of the development and the elaboration of the planning as well as the orientation of the development and the elaboration of the planning are revealed. Finally, the insights of acad. E. Mateev about the criteria for teaching the material in the area of forecasting and planning are revealed.